2009
DOI: 10.1007/bf03179226
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of opsonophagocytic activity of antibodies specific toNeisseria meningitidis serogroup A capsular polysaccharide-serogroup B outer membrane vesicle conjugate in animal model

Abstract: Neisseria meningitidis is efficiently phagocytosed by polymorphonuclear leukocytes (PMN S ) following opsonization with opsonic antibodies; opsonophagocytosis is the primary mechanism for clearance of meningococci from the host. Thus, in testing meningococcal vaccines, the level of opsonophagocytic antibodies appears to correlate with vaccine-induced protection. Our previous studies demonstrated that the conjugation of N. meningitidis serogroup A capsular polysaccharide (CPSA) to serogroup B outer membrane ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, the potency of OMV as a carrier (conjugated to a hapten) is now proven. Overall, previous studies have shown that the predominant outer membrane proteins (PorA, PorB and RmpM) from N. meningitidis present in the Meningococci B Cuban vaccine had different capacities to prime the immune responses [1,13–16] .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, the potency of OMV as a carrier (conjugated to a hapten) is now proven. Overall, previous studies have shown that the predominant outer membrane proteins (PorA, PorB and RmpM) from N. meningitidis present in the Meningococci B Cuban vaccine had different capacities to prime the immune responses [1,13–16] .…”
Section: Introductionmentioning
confidence: 79%
“…OMVs were prepared as previously described [2,6,14] . N. meningitidis serogroup B strain CSBPI and G-245 cells were grown in 40 L modified Frantz medium in a fermenter for 24 hours at 36°C.…”
Section: Methodsmentioning
confidence: 99%
“…Covalent linkage of PS or LPS to carriers such as proteins produce glycol-conjugates which are T-dependent antigens and prime for long lasting immunity with either PS or LPS. On the other hand, PS or LPS-protein conjugates have been proven to be effective in several cases while well-defined glycoconjugate vaccines have also been explored with an intention to elicit discriminating immune responses [16,21,22,29]. The latest study in brucellosis vaccines have employed a conjugated B. abortus LPS with GB-OMV which could induce both humoral and cellular immune responses against Brucella spp [17].…”
Section: Omv As a Carrier In Conjugated Vaccinesmentioning
confidence: 99%
“…We previously synthesized a conjugate vaccine candidate with group A meningococcal capsular polysaccharide (GAMP) conjugated to OMV, which was immunogenic in rabbits, and the respective antisera showed bactericidal and opsonophagocytic activity against N. meningitidis serogroup A, [10][11][12] but the method of conjugation is very complex and needs to be controlled by multiple parameters in light of the risk of conformational changes of dominant and essential epitopes as a result of the covalent reactions between GAMP and OMV. In this respect, protective antibodies against native polysaccharide or OMV proteins would not be induced following this conformational change.…”
Section: General and Specific Adjuvant Properties Of Gbomv In Meningomentioning
confidence: 99%